2022
DOI: 10.1186/s12961-022-00915-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of unmet needs for hypertension care among the older population in Selangor: cross-sectional study

Abstract: Background Hypertension is a major cause of morbidity and mortality worldwide. Although multiple studies have assessed the prevalence of hypertension among older people, no study has examined the unmet need for hypertension care among older people in Malaysia. This study uses the hypertension care cascade to identify the prevalence of unmet needs for hypertension care and their determinants among the older population in Selangor. Methods This is a cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The studies in Malaysia [12] and Myanmar [13] adapted the survey questionnaire from the Japan Gerontological Evaluation Study [14] to gather basic information about the health and social conditions of the older population, including blood pressure measurements. The two papers from these studies used different analytical approaches, and both found a high prevalence of hypertension and unmet needs for hypertension diagnosis in their populations.…”
Section: Research To Accelerate Uhc In the Context Of Global Populati...mentioning
confidence: 99%
“…The studies in Malaysia [12] and Myanmar [13] adapted the survey questionnaire from the Japan Gerontological Evaluation Study [14] to gather basic information about the health and social conditions of the older population, including blood pressure measurements. The two papers from these studies used different analytical approaches, and both found a high prevalence of hypertension and unmet needs for hypertension diagnosis in their populations.…”
Section: Research To Accelerate Uhc In the Context Of Global Populati...mentioning
confidence: 99%